TbAGO1, an Argonaute protein required for RNA interference, is involved in mitosis and chromosome segregation in Trypanosoma brucei - Bastin Philippe; Durand-Dubief Mickaël (BMC Biology, 2003)
Abstract Background RNA silencing processes are widespread in almost all eukaryotic organisms. They have various functions including genome protection, and the control of gene expression, development and heterochromatin formation. RNA interference (RNAi) is the post-transcriptional destruction of RNA, which is mediated by a ribonucleoprotein complex that contains, among several components, RNA helicases and Argonaute proteins. RNAi is functional in trypanosomes, protozoan parasites that separated very early from the main eukaryotic lineage and exhibit several intriguing features in terms of the control of gene expression. In this report, we investigated the functions of RNAi in Trypanosoma brucei. Results By searching through genome databases, novel Argonaute-like proteins were identified in several protozoa that belong to the kinetoplastid order, a group of organisms that diverged early from the main eukaryotic lineage. T. brucei possesses two Argonaute-like genes termed TbAGO1 and TbPWI1. Dual transient transfection assays suggest that TbAGO1, but not TbPWI1, is involved in RNAi. The entire coding region of TbAGO1 was deleted by double gene knockout. TbAGO1-/- cells turned out to be completely resistant to RNAi generated either by transfected double-stranded RNA or by expression of an inverted repeat. TbAGO1-/- cells were viable but showed a dramatically reduced growth rate. This was probably due to defects in mitosis and abnormal chromosome segregation as revealed by in situ analysis. The RNAi and growth phenotypes were complemented by the inducible expression of a GFP::TbAGO1 fusion protein that revealed the cytoplasmic location of the protein. Conclusions The requirement of TbAGO1 for RNAi in trypanosomes demonstrates the evolutionary ancient involvement of Argonaute proteins in RNAi silencing processes. RNAi-deficient TbAGO1-/- cells showed numerous defects in chromosome segregation and mitotic spindle assembly. We propose a working hypothesis in which RNAi would be involved in heterochromatin formation at the centromere and therefore in chromosome segregation.